A glomerulus chip with spherically twisted cell-laden hollow fibers as glomerular capillary tufts. (1st July 2023) - Dai, Zhilin; Li, Chengpan; Shi, Zhengdi; Li, Shibo; Luo, Tianzhi; Ding, Weiping
Abstract: Glomerulus-on-a-chip, as a promising alternative for drug nephrotoxicity evaluation, is attracting increasing attention. For glomerulus-on-a-chip, the more biomimetic the chip is, the more convincing the application of the chip is. In this study, we proposed a hollow fiber-based biomimetic glomerulus chip that can regulate filtration in response to blood pressure and hormone levels. On the chip developed here, bundles of hollow fibers were spherically twisted and embedded in designed Bowman's capsules to form spherical glomerular capillary tufts, with podocytes and endotheliocytes cultured on the outer and inner surfaces of the hollow fibers, respectively. We evaluated the morphology of cells, the viability of cells, and the metabolic function of cells in terms of glucose consumption and urea synthesis by comparing the results obtained under fluidic and static conditions, confirmed the barrier function of the endotheliocyte-fiber membrane-podocyte structure by monitoring the diffusion of fluorescein isothiocyanate (FITC)-labeled inulin, albumin and IgG, and, for the first time, achieved on-chip filtration regulation in response to the hormone atrial natriuretic peptide. In addition, the application of the chip in the evaluation of drug nephrotoxicity was also preliminarily demonstrated. This work offers insights into the design of a more physiologically similar glomerulus on a microfluidic chip.